The surface protein HvgA mediates group B streptococcus hypervirulence and meningeal tropism in neonates - Tazi, Asmaa; Disson, Olivier; Bellais, Samuel; Bouaboud, Abdelouhab; Dmytruk, Nicolas; Dramsi, Shaynoor; Mistou, Michel-Yves; Khun, Huot; Mechler, Charlotte; Tardieux, Isabelle; Trieu-Cuot, Patrick; Lecuit, Marc; et al. (The Journal of experimental medicine, 2010)
Streptococcus agalactiae (group B streptococcus; GBS) is a normal constituent of the intestinal microflora and the major cause of human neonatal meningitis. A single clone, GBS ST-17, is strongly associated with a deadly form of the infection called late-onset disease (LOD), which is characterized by meningitis in infants after the first week of life. The pathophysiology of LOD remains poorly understood, but our epidemiological and histopathological results point to an oral route of infection. Here, we identify a novel ST-17–specific surface-anchored protein that we call hypervirulent GBS adhesin (HvgA), and demonstrate that its expression is required for GBS hypervirulence. GBS strains that express HvgA adhered more efficiently to intestinal epithelial cells, choroid plexus epithelial cells, and microvascular endothelial cells that constitute the blood–brain barrier (BBB), than did strains that do not express HvgA. Heterologous expression of HvgA in nonadhesive bacteria conferred the ability to adhere to intestinal barrier and BBB-constituting cells. In orally inoculated mice, HvgA was required for intestinal colonization and translocation across the intestinal barrier and the BBB, leading to meningitis. In conclusion, HvgA is a critical virulence trait of GBS in the neonatal context and stands as a promising target for the development of novel diagnostic and antibacterial strategies.